Emergence of India as a Key Player in Global Economic Affairs - Mukesh Kumar Mishra (ResearchGate, 2024)
India is indeed the world's largest democracy with a population exceeding 1.4 billion people. The country has experienced significant economic growth over the past few decades, and its integration into the global economy has played a crucial role in this transformation. On February 7, 2015 PM Narendra Modi given an approach aligns with India's vision of a self-reliant and influential India that actively participates in international forums, addresses global challenges, and contributes to the shaping of global narratives (Brueau, 2015). Realizing these advantages requires efforts such as, sustainable transition, policy support, and adaptability to changing global dynamics. Additionally, addressing challenges such as infrastructure gaps, regulatory complexities, and socio-economic disparities will be crucial for sustaining and maximizing the potential benefits of these advantages. The paper identifies key areas that will accelerate India's growth over the next decade and vision for India's sustainable economic growth and ways to increase its role in the global economy due to its political and strategic importance in the evolving post-COVID-19 pandemic new economic order.
Keywords: 330; Global Economy; Sustainable Economy